Kombucha Based on Javanese Turmeric (Cucurma zanthorrhiza and Cucurma zedoaria): Effect of Various Concentrations and Antioxidant Activity - Zubaidah, Elok; Kusmiyati, Nur; Arum, Mentari Sekar; Hasfiani, Yuliatin; Sujuti, Hidayat (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2025)
Temulawak (C.zanthoriza) and white turmeric (C.zedoaria) are Indonesian herbal plants widely used to treat various diseases including anti-inflammatory properties, neuroprotective, nephroprotective, antitumor, and hepatoprotective. A long-standing tradition, Kombucha is a drink produced by fermenting tea using combine of lactic acid bacteria, acetic acid bacteria and mold. It's classified as a functional food due to its high antioxidant and antibacterial activity, suggesting potential benefits for disease prevention.This research aims to improve the functional value of kombucha by using temulawak and white turmeric. Kombucha is made from temulawak and white turmeric powder with various concentrations ranges 0.2 – 1% (w/v)) and a sugar concentration of 10% (v/v)). After 8 days of fermentation, temulawak and white turmeric kombucha were tested for pH, total acid, amount of phenol, and IC50. The effect of various concentrations temulawak and white turmeric as a substrate for kombucha demonstrated significant (p0.05) in reduction of pH, increased total phenol content, IC50 value of antioxidant activity, also increased total acid. The best treatment of temulawak and white turmeric kombucha was obtained at a concentration of 1% with a pH of 2.77 for temulawak kombucha and 2.80 for white turmeric kombucha; total acid of 4.38% for temulawak kombucha and 3.60% for white turmeric kombucha; total phenols were 232.48 mgGAE/ml for temulawak kombucha and 113.00 mgGAE/ml for white turmeric kombucha; The IC50 value was 30.82 ppm for temulawak kombucha and 40.15 ppm for white turmeric kombucha.